Integration of Bond Markets and Portfolio Diversification : Evidence from the 2008 Global Financial Crisis - Patel, Ritesh J.; Gandhi, Divyesh J.; Patel, Mitesh K.; Modi, Tejas M. (Indian Journal of Finance, 2023)
Purpose : This study aimed to examine the integration between the bond markets of the MSCI Emerging Markets and the USA concerning the 2008 financial crisis. Methodology : Granger causality and correlation tests were used to assess the short-term integration of the bond markets. The long-term integration was examined using the Johansen co-integration test and VAR analysis. Findings : Post-crisis, bond markets became more correlated with each other. Due to a lack of market integration in both periods, different portfolio combinations offered the chance for portfolio diversity. The MSCI Emerging Asian markets and US market integration increased with the global financial crisis of 2008. The results of the VAR analysis and impulse response analysis found that innovations in the markets of the USA and China affected the Indian market the most; whereas, the rest of the market had a nominal impact. Practical Implications : The study has practical implications in the sense that based on the integration, investors might diversify their holdings to achieve a better risk-return balance. The investors can design their investment portfolio accordingly to have an optimal portfolio. Originality : This study focused on building portfolio diversification with fixed-income securities.